Monitoring the Burden of the Antibiotic Resistance and Virulence Genes in Pet Animals Suffering from Bacterial Otitis - Mayson Hamdy; Soliman Mohammed; Haithem Farghali; Hassan Aboul-Ella; Sherif Marouf (Journal of Applied Veterinary Sciences, 2025)
The etiology of otitis in dogs and cats is multifactorial and complex, involving bacterial and fungal pathogens. This study aimed to describe microbiological features and susceptibility profiles of bacterial pathogens associated with 212 cases of external otitis, comprising 118 dogs and 94 cats. Ear swabs were processed to identify bacterial etiologies following standard microbiological methods, followed by antibiotic sensitivity profiling of each obtained isolate and PCR screening for a list of virulence and resistance genes. The overall resistance incidence for the obtained isolates against amoxicillin was 3.8%, amoxicillin/clavulanic acid was 55.4%, ceftriaxone was 26.6%, ceftazidime was 27.5%, cefoperazone (22.9%), enrofloxacin (1.6%), gentamicin (9.9%), amikacin (7.2%), linezolid (92.8%), tylosin was 76%. PCR screening of isolated bacteria revealed that E. coli and K. pneumoniae harbored ESBL genes like blaTEM, blaCTX-M, and other resistance genes aadB and qnrB. Likewise, the other Gram-negative isolates of P. aeruginosa and P. mirabilis were also positive for the same resistance genes. Gram-positive S. aureus harbored blaZ and norA resistance genes. Current work provides priceless surveillance value in monitoring resistant bacteria in pet animals as Customized monitoring programs can help identify certain AMR frameworks, aid clinicians in making logical treatment choices, and restrict the selection and spread of AMR within the population.